ADONHERS (Aged DONor HEart Rescue by Stress echo) protocol for heart donation from marginal donor hearts: monocentric retrospective study on recipients survival after 10-year follow-up. (3rd October 2022) - Mandoli, G E; Barilli, M; Soviero, D; Ghionzoli, N; Maccherini, M; Bernazzali, S; Natali, B; Cavigli, L; D'Ascenzi, F; Focardi, M; Pastore, M C; Valente, S; et al.
Abstract: Purpose: Amelioration of therapies and increased survival in heart failure (HF) is leading to a growing number of patients affected by advanced HF, with an overall 1-year prognosis ranging from 25 to 75%. The gold standard treatment for end stage HF is heart transplantation (Htx), but lack of organs donors remains an important limitation. Marginal hearts can potentially improve and be utilized after a re-evaluation by "aggressive" assessment of donor left ventricular dysfunction, with an important increase of utilization rates (from 38–59%) in the latest years. In our study we analysed if recipients of marginal donor hearts, selected by dipyridamole stress echocardiography, had different outcome compared to recipients with acceptable donor hearts. Methods: Data collected from 2006 and 2014 of patients who received orthotopic Htx were retrospectively analysed. Clinical, laboratory and instrumental features were evaluated and patients with homogenous baseline characteristics were selected to reduce biases among the two groups. Dipyridamole stress echo was performed on donors >55 years old or <55 with comorbidities/mildly dysfunctional left ventricle. Results: Twenty-two recipients were included (eleven patients with a marginal donor heart, group 1, and eleven with acceptable donor heart, group 2). Mean donors age was 41±23, 45±29 years for group 1 vs 36±12 for group 2. The average follow-up was 113 months. Age, cardiovascular risk and morpho-functional characteristics of the left ventricle were comparable between the two population (P>0.05) (see Table 1). Left atrial size was significantly higher in marginal hearts (Optimal: p=0.007; Marginal: p=0.003). Optimal donors showed a higher impact of CAV (p=0.019) together with more elevated values of cholesterol and triglycerides (p=0.048 and p=0.012 respectively). No rejection differences were found between the two groups. Four patients deceased, 3 had received a standard donor heart and 1 was from the marginal donor group, with and overall median time to death of 124 months. Conclusions: No mortality difference was detected among the two heart donor groups with a lower incidence of CAD in the marginal heart donor population. Our study shows how Htx from selected marginal donor heart can implement shortage of organs without difference in survival with acceptable donor hearts. Funding Acknowledgement: Type of funding sources: None.